Message Theory: A Comparative Analysis between Western and Islamic Perspectives - Taqiyuddin, Muhammad; Zarkasyi, Hamid Fahmy; Ihsan, Nur Hadi (Jurnal Komunikasi Islam, 2024)
The Islamic scholarly tradition is rich in fundamental related-communication concepts, including message theory. This article endeavors to undertake a comparison analysis of seminal concepts of message between Islam and Western perspectives in the field of communication science. Employing a library research approach and semiotics perspective, this study argues that aspects of the messages, that is, 'the subject of message' and 'the messenger,' have roots in the theological dimensions of Islam. This differs from the Western concept of messages, which tend to solely rational-empirically explain messages as themselves. However, some seminal concepts about messages in Islamic literature can be integrated into theories of messages in modern communication theory that are relevant to current the Islamic-based scholarly paradigm, namely the comparative-integrative framework.